The Importance Of Agricultural Instructors In Sharing Millennial Farmers' Interest With The Intervening Variable Of Agriculture Technology Modernization In The Sawit Seberang Prosperous Farmer Group - Junaidi, Junaidi (Jurnal Ekonomi, 2024)
The waning enthusiasm of the younger generation towards pursuing careers in the agriculture industry is a cause for concern. This situation poses a significant risk to Indonesia's agricultural future, particularly in the realms of economic and food security. We need a plan that utilizes the knowledge and skills of agricultural teachers to gain a deep understanding of the urgent demands of the agriculture industry. Various instructor positions have considerable potential to increase the millennial generation's enthusiasm for agriculture, both as instructors and in spreading knowledge and advancements. Hence, it is imperative to prioritize these positions as a means to foster the millennial generation's enthusiasm for agriculture. The Makmur farmer group in Sawit Seberang actively took part in this study endeavor. A total of 120 samples were utilized. The researchWe employed a quantitative research methodology, employing primary data acquired through the dissemination of pre-designed study questionnaires. The findings indicate that the involvement of extension workers has a beneficial effect on the interests of the millennial cohort of farmers.